Catch assessment of commercially important gastropods in Guang-Guang, Mati City, Davao Oriental, Philippines - Imee Maynawang; Edison Macusi (Academia Biology)
Gastropods are one of the most valuable seashells, and they have high economic and nutritional value. This study aimed to assess the value and uses of commercially harvested gastropods, including species composition, time of gleaning, and methods used to harvest the gastropods in their habitat. To do that, data were collected by monitoring the catch of selected gleaners and by using semi-structured questionnaires. The survey interview was conducted in Guang-Guang, Mati, Davao Oriental, with N = 60 respondents while the actual monitoring of selected gleaners and their catch was conducted from February to April on three random days in a week during the low tide period (N = 30). The result of the study showed that the most abundant gastropod species caught by gleaners belong to the family of Strombidae, Cerithiidae, Nassaridae, and Neritidae. Gleaners mostly catch the little bear conch (Strombidae), which was the most abundant gastropod in the area, and sold immediately in the market and their neighborhood. Gleaners take 2-3 hours a day to harvest and gain an income of PHP 200—350; the catch per unit effort of gleaners ranged from 0.30 to 0.50 kg/hour of daily gleaning. Results comparing the species, weight, and count of gastropods showed significant differences (P ≤ 0.05). The top three species caught are little bear conch with a monthly mean count of 38,447 (732 kg) followed by the horn shell with 12,714 (129 kg) and nassa mud snail with 3627 (32 kg). The gastropods were exploited in various sizes such as the little bear conch at a size of 36—40 mm, horn shell at a size of 36—45 mm, and the nassa mud snail at a size of 21—25 mm. Based on the assessment, the gastropods in Guang-Guang have a high exploitation level of gleaning and need policy interventions for their protection.